Cyclin-Dependent Kinase Inhibition by Flavoalkaloids - K. Jain, S.; B. Bharate, S.; A. Vishwakarma, R. (Mini Reviews in Medicinal Chemistry, 2012)
Chromone alkaloids and flavoalkaloids are an important group of natural products possessing promising medicinal properties. A chromone alkaloid rohitukine is a major bioactive chemical constituent of plant Dysoxylum binectariferum (Meliaceae) Hook. which is phylogenetically related to the Ayurvedic plant, D. malabaricum Bedd. used for treatment of rheumatoid arthritis. This chromone alkaloid led to discovery of two synthetic flavoalkaloids: flavopiridol (Sanofi) and P-276-00 (Piramal) which have reached to advanced stages of clinical development for cancer treatment. Flavopiridol (Alvocidib; L868275; HMR-1275; NSC 649890 of Sanofi-Aventis + NCI) is approved as an orphan drug for treatment of chronic lymphocytic leukemia and is currently undergoing phase II studies as monotherapy and also as in combination regimes with traditional chemotherapy agents. P-276-00 (12) is currently in phase II clinical studies for advanced refractory neoplasms and multiple myeloma. Extensive amount of medicinal chemistry efforts have been reported on these flavoalkaloids. Flavopiridol demonstrated potent and specific in vitro inhibition of variety of cyclindependent kinases with clear block in cell cycle progression at the G1/S and G2/M phases. Preclinical studies demonstrated the capacity of flavopiridol to induce programmed cell death, promote differentiation, inhibit angiogenic processes and modulate transcriptional events. The co-crystallised structure of deschloro-flavopiridol with CDK-2 is available and key interactions in the ATP binding site have been reported. Flavopiridol has also been studied for the treatment of arthritis and atherosclerotic plaque formation. The present review comprises discovery, medicinal chemistry, pharmacology and preclinical/clinical development of flavoalkaloids as CDK inhibitors.
Keywords: 2-chlorobenzoyl chloride